One-Day Behavioral Intervention for Distressed Veterans with Migraine: Results of a Multimethod Pilot Study. Issue 7 (28th June 2018) - Huddleston, C; Martin, L; Woods, K; Dindo, L
Abstract: Introduction: Migraine, a chronic neurological disorder characterized by episodic severe headache pain and functional impairment, affects approximately 12% of the general US population. Veterans returning from Iraq or Afghanistan have two to four times the incidence of migraine of the general population. Veterans with migraines are more than twice as likely to have comorbid psychiatric conditions as veterans without migraines, with depression and post-traumatic stress disorder being most prevalent. This psychiatric–migraine comorbidity is of major public health significance, as it leads to decreased quality of life, poorer response to migraine and mental health treatment, and overall worse prognosis. Unfortunately, acceptable and effective treatments for these comorbid problems have rarely been investigated. The aims of this study are to examine the acceptability, feasibility, and preliminary efficacy of a 1-d acceptance and commitment therapy (ACT) plus Migraine Education workshop. Method: Twenty-five veterans with migraines and co-occurring depression and/or anxiety completed the 1-d ACT plus Migraine Education workshop. Veterans completed assessments of depressive and anxiety symptoms, general functioning, headache-related disability, and ACT-specific skills at baseline and 3 mo after the workshop. Changes from baseline to 3-mo follow-up on the self-report and clinician-rated measures were assessed using the paired t -test and Wilcoxon signed-rank test. Veterans also completed semistructured qualitative interviews documenting their experiences with the workshop 2 wk and 3 mo following the intervention. Qualitative data were analyzed via directed content analysis. Individual codes were aggregated into larger themes agreed upon by consensus. Results: At 3-mo follow-up, veterans significantly improved in depressive and anxiety symptoms, general functioning, and headache-related disability compared with baseline. Additionally, veterans significantly improved in pain acceptance and engagement in valued life areas. In interviews, veterans indicated that the migraine education helped them feel more knowledgeable about their condition, and this empowered them to better manage their headaches, including talking to their physician about medication adjustments. The ACT component led to greater awareness of the role stress plays in exacerbating pain and ways to manage this stress, including greater acceptance and greater engagement in valued life activities. For some, however, the role of stress in exacerbating migraines needed to be highlighted more. Veterans appreciated being in a group with other veterans with similar health difficulties and wanted this to be incorporated into ongoing care at the Veterans Affairs medical center. The patient education manuals were useful to the veterans, with some referring to them during the months following the workshop. Conclusion: Findings of this small trial have important implications pending replication in a more rigorously designed large-scale study. A 1-d ACT plus Migraine Education workshop is an acceptable and feasible treatment approach for veterans with migraines and significant distress. Significantly reduced distress and disability, as well as improved coping skills, suggest that veterans were activated to engage more fully in their lives and clinical care. The availability of an effective transdiagnostic intervention that can be completed in 1 d is particularly valuable for veterans who have multiple comorbid conditions and who encounter practical barriers to engaging in the usual prescribed weekly therapy treatments.